The relationship between motivation and employee performance: David McClelland theory of needs / Nur Izzati Hassan - Hassan, Nur Izzati (2013)
This study examines to find out the significant relationship between different motivation factors used by the employees of the organization and their effects on the performance and efficiency of employees. The researcher used quantitative method to analyze deeply the three terms used in the theory of needs by David McClelland. The researcher will present the positive and negative relationship between the independent variables, in the sense that how motivation factor increase and stimulate the working performance of organization’s employees. The relationship between motivation factors and employees performance is a much significant and debatable issue in the current period. In this quantitative analysis using the following motivation factors which is the need for achievement, the need for affiliation and the need for power. Using the questionnaire survey, the study gathered respondents of 132 employees that come from six departments which are the Management Department, Customer Service Department, Legal Enforcement Department, Registration and Vehicle Licensing Department, Driving and Testing Licensing Department, and Automotive Department. These motivational factors were also significantly positive regarding to the employees answers to the questionnaire. Likewise, the motivational factor which are the need for achievement, the need for affiliation and the need for power were significantly positively related to the employees performance rating by the employees from the six departments in Road Transport Department (RTD) Kuala Terengganu.